A125 PERICARDITIS AND 5-ASA EXPOSURE IN INFLAMMATORY BOWEL DISEASE: TWO PAEDIATRIC CASE REPORTS. (1st March 2018) - Lozano Ruf, A; Walters, T D; Church, P
Abstract: Aims: 5-aminosalicylic acid-containing products are often used as first-line treatment in inflammatory bowel disease (IBD). Pericarditis has been reported as a rare extraintestinal inflammatory manifestation of IBD and as a side effect of 5-ASA, when it usually occurs soon after starting the drug. Clinical presentations range from asymptomatic pericardial effusions to potentially life-threatening cardiac tamponade. Recognition as a possible side effect of 5-ASA necessitating cessation is important. Methods: We report two paediatric cases presenting with chest pain and fever, elevated cardiac enzymes and electro/echocardiographic evidence of pericarditis. Infectious causes of pericarditis were excluded. Results: One of the patients received 5-ASA for one month prior to developing pericarditis, whereas the other received 5-ASA for eighteen months. In the second case, the patient soon had a flare of colitis symptoms, and so treatment was restarted five days later. Pericarditis symptoms recurred within six days and 5-ASA was immediately stopped with prompt resolution of symptoms. Both patients then went on to receive maintenance therapy with infliximab, with good effect. Conclusions: Pericarditis in inflammatory bowel disease is a rare occurrence with a multifactorial origin. The pathophysiology of 5-ASA induced pericarditis is not completely understood. Treatment includes prompt cessation of the drug, supportive care, and close monitoring for complete resolution of cardiovascular symptoms. Given the common use of 5-ASA in the treatment of IBD, physicians should keep this potentially severe complication in mind. Funding Agencies: CAG